THE SIMULATION AND OPTIMIZATION OF LIFT CONTROL SYSTEMS WITH GENETIC ALGORITHMS - Bolat, Berna (YILDIZ TECHNICAL UNIV, 2006)
In tall buildings where there is heaving traffic, the service offered by multi-car lift systems is qualitatively sufficent. Besides, the lifts are expected to work fast, efficiently and without waiting and not affecting the activities of the building negatively. It has become possible to apply computer-based group control systems for the liftts to function with high performance quantitatively. In this paper, the simulation and optimization of the lift control systems with genetic algorithms have been taken into consideration and an explanatory example has been given by introducing the developed software.
Keywords: Lift; lift control systems; genetic algorithms; Engineering